2019
DOI: 10.1007/s10661-018-7175-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation of heavy metal contamination and its potential sources along the major urban wastewater channel in Kampala, Uganda

Abstract: Heavy metal pollution from untreated industrial wastewater has become a major concern to the environment and public health in many rapidly growing cities in low-income countries. Previous studies on heavy metals of urban wastewater systems have focused on long-term (weekly or seasonal) variations, while only few studies investigated short-term (daily) variation to capture potential bulk discharges. To monitor and enforce wastewater discharge regulations and reduce industrial pollution, a better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Second, the sewage management system needs to be improved at the city level along with the industrial waste (Dietler et al, 2019). Much research proposed to manage the storm and sewage water by adding to the ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sewage management system needs to be improved at the city level along with the industrial waste (Dietler et al, 2019). Much research proposed to manage the storm and sewage water by adding to the ponds.…”
Section: Discussionmentioning
confidence: 99%
“…A cluster analysis method was adopted in this study, and the sampling points were divided into CA1, CA2, CA3, and CA4 Groups. These groups were composed of sampling points (4,32,33,34,35); (5,6,7,8,11,16,18,24,25,27,28,31,36,37,38); (9,12,13,14,15,19,20,21,22,23,29); and (1,2,3,10,17,26,30), respectively, as detailed in Figure 3. Table 3 shows that, with the exception of the T, pH, TP, and Zn, there were significant differences in the heavy metals and nutrients among the different groups.…”
Section: Cluster and Discriminant Analysesmentioning
confidence: 99%
“…Previous research results have shown that agricultural activities are the main sources of suspended solids and inorganic nutrients (phosphate and nitrate) in rivers, and agricultural fertilization is also considered the main source of heavy metals [4][5][6]. In addition, industrial wastewater contains a variety of heavy metals [7][8][9], and municipal discharges will also have significant impacts on the nutrient elements and heavy metal content in rivers [10][11][12]. Nutrients and heavy metals pollution in rivers will not only lead to the loss of biodiversity and environmental degradation, but also pose a serious threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are among the most abundant pollutants in liquid industrial effluents; these compounds have high potential of toxicity and are highly dangerous to ecosystems and human health. Most of these heavy metals are present in polluted waters including Hg, Pb, Ag, Cu, Cd, Cr, Zn, Ni, Co and Mn (Bhuiyan et al, 2011), and it has been found that many heavy metal ions produce strong health problems and damage plants and animals (Nahar et al, 2018;Dietler et al, 2019).The dangers of pollution of some heavy metals may be acute due to their severe toxicity even at low concentrations (Christensen et al, 2000;Jarup, 2003).…”
Section: Introductionmentioning
confidence: 99%